Human Capital and Education: The State of the Art in the Economics of Education - Simon Burgess (Institute for the Study of Labor (IZA), 2016)
This review describes the research frontier on human capital and education in economics research. It delineates what is known and largely agreed, and what are the most promising lines for future research. The approach will be to explain clearly and precisely the research evidence, in a way that makes this accessible to a wide audience. The survey has two particular aims. First, it draws out the implications for key education policy issues, highlighting which policy ideas can be supported by the economics research. To do this, my focus is on research that identifies causal effects. Second, it tries to identify some of the big open research questions and policy knowledge gaps in this field.
Keywords: I20; 330; education; human capital